Analisis Manajemen Risiko Keuangan dan Implementasi Strategi pada Perusahaan Travel Internasional: Studi Kasus Mytravelink Bandung - Kamaludin, Asep; Jabbar, Bella Hidayat Rohul; Sobana, Dadang Husen (Economic Reviews Journal, 2025)
In the modern financial landscape, risk is an inevitable element that must be managed systematically to maintain corporate stability. Risks emerge from uncertainties driven by internal and external factors such as market volatility, government policies, and global economic fluctuations. This study aims to examine the concept of financial risk and relevant mitigation strategies for financial institutions and corporations, illustrated through a case study of MyTravelink, an international travel company based in Bandung. Using a descriptive qualitative approach through library research and empirical case analysis, data were collected from academic literature, official regulations, and direct observations of foreign exchange risk at MyTravelink. The findings reveal four main categories of financial risk, market, credit, liquidity, and operational, each requiring different mitigation strategies, including hedging, portfolio diversification, and strengthening corporate governance (GCG). The MyTravelink case shows how euro-to-rupiah exchange rate fluctuations during global crises increased operational costs, and how hedging strategies combined with adaptive contract policies effectively reduced potential losses. The study highlights the importance of a structured risk management process, identification, measurement, control, and monitoring, supported by decision-making theories such as Classical Decision Theory, Prospect Theory, and Contingency Theory. A consistent and adaptive risk management culture is essential for maintaining financial resilience and sustaining business opportunities.